2021
DOI: 10.3348/kjr.2020.0984
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Assessment of Renal Sinus Invasion by Renal Cell Carcinoma according to Tumor Complexity and Imaging Features in Patients Undergoing Radical Nephrectomy

Abstract: Objective To identify the association between renal tumor complexity and pathologic renal sinus invasion (RSI) and evaluate the usefulness of computed tomography tumor features for predicting RSI in patients with renal cell carcinoma (RCC). Materials and Methods This retrospective study included 276 consecutive patients who underwent radical nephrectomy for RCC with a size of ≤ 7 cm between January 2014 and October 2017. Tumor complexity and anatomical renal sinus invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…36 SFI is the principal route for the extrarenal extension of RCC and is a prognostic factor for poor recurrence-free and overall survival after nephrectomy. 16,37 These findings are consistent with our result showing that the ctDNA detection rate was higher in patients with SFI.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…36 SFI is the principal route for the extrarenal extension of RCC and is a prognostic factor for poor recurrence-free and overall survival after nephrectomy. 16,37 These findings are consistent with our result showing that the ctDNA detection rate was higher in patients with SFI.…”
Section: Discussionsupporting
confidence: 92%
“…5,32 Although the PADUA system can predict fat invasion to some extent, it is not sufficient to predict SFI or PFI. 37 As this system was originally designed for evaluating the surgical complexity and morbidity of PN, 13 the nephrometry system may be insufficient to predict SFI because tumor building into the renal sinus may not necessarily be a result of SFI. 37 The role of ctDNA has primarily been investigated in the monitoring of tumor progression during treatment because of the advantages of non-invasive ctDNA sampling methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, Chou et al [ 33 ] found that nonsmooth tumor margin is a promising two-dimensional imaging feature for preoperative assessment of microvascular invasion (MVI). In patients with renal cell carcinoma (RCC), the presence of an unsmooth margin or a finger-like protrusion is a CT-based tumor feature that can be used to predict pathologic renal sinus invasion (RSI) preoperatively [ 38 ]. These two studies suggest that tumor margin morphology has the potential to predict LVI status.…”
Section: Discussionmentioning
confidence: 99%
“…When 34 original research studies reporting OR published in the Korean Journal of Radiology in 2020–2021 [ 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] were evaluated against a rigorous standard (i.e., complete transparency in reporting), 91.2% (31/34) clearly mentioned how they defined the odds, 62.1% (18/29) unmistakably described the reference category for OR calculation for categorical variables, and 42.9% (9/21) specified the one-unit amount for OR for continuous variables. Therefore, there is room for improvement in reporting.…”
Section: How To Calculate and Report Ormentioning
confidence: 99%